Crise cotonnière en Centrafrique et choix des agriculteurs en fonction de leur localisation par rapport à la ville - Mbétid-Bessane, E. (Tropicultura, 2003)
Cotton Crisis in Central African Republic and Choice of Farmers According to their Location to the City. A study on the choice cropping pattern by farmers as compared to their location to the city, following the cotton crisis of 1998, has been conducted in Central African Republic. After having chosen 92 producer groups around two cities distributed in 4 concentric circles, a collection of statistics and surveys have been realised during three agricultural campaigns. Regressions of surfaces and production to distances of farms to the city have been calculated. Results show the dependence between cultivated surfaces, production and distance to the city. The more a farm is far from the city, the more its cotton surface and its production increase while the share of food crops surface decreases. An increase by 10 km of the position of a farm from the city entails an increase by 5.8 ares of its cotton surface and by 58.8 kg of its cotton production while a diminution of 4% is observed in the surface of food crops. Farms located far from the city choose a cotton strategy while those located close to the city choose to develop a "food crops" strategy. The local socio-economic context of farms in term of proximity to the market plays a determining role in the decision-making of farmers.